Unravelling external perturbation effects on the optical phonon response of graphene. (19th January 2018) - Bendiab, Nedjma; Renard, Julien; Schwarz, Cornelia; Reserbat‐Plantey, Antoine; Djevahirdjian, Léo; Bouchiat, Vincent; Coraux, Johann; Marty, Laëtitia
Abstract : Raman spectroscopy is a powerful and nondestructive probe that demonstrates its efficiency in revealing the physical properties of low‐dimensional sp 2 carbon systems. It gives access to the number of layers, the quality and the nature of defects of all carbon allotropes, but also to the understanding of the influence of perturbations such as strain and/or doping. In this paper, we review the state of the art regarding the effect of external perturbations on the optical phonons of graphene. We describe how doping can tune the unusual electron–phonon coupling in graphene and thus modify not only the resonance conditions but also the phonon intensities thanks to quantum interferences. We also review the impact of strain on optical phonons and how one can disentangle strain and doping thanks to optical phonons. Last, implementations of this field to strain engineering or to graphene‐based mechanical resonators will be presented. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : As a one‐atom‐thick material, graphene is extremely sensitive to interaction with its environment. The Raman spectrum of graphene provides quantitative information about strain and doping resulting from external stimuli. This review addresses the Raman response of graphene under external perturbation.